Endometriosis of the abdominal wall - Alvarez, María del Pilar; Carriquiry, Luis (Cirugía del Uruguay, 2003)
Endometriosis of abdominal wa/1 is a rare entity, wich frequently appears after gynecological surgery. Case history includes three cases of parietal endometriosis wich were treated in Maciel Hospital of Montevideo.